Discards for Southern Hake Stock, a First Approach to Iberian Data - Fernandes, Ana Claudia; Pérez-Contreras, María Nélida; Barbosa, Susana; Silva, Dina; Araujo-Fernández, María Hortensia; Jardim, Ernesto; Ferreira, Ana; Sousa, Vera; Pestana, Graça (2005)
This document presents sampling levels obtained with Portuguese and Spanish Discard Sampling Programmes, both included in National Sampling Programmes, and some preliminary results for the Iberian Southern Hake discards. These programs consist on onboard-observer sampling schemes, with co-operative vessels, quasirandom selected, in the ICES Division VIIIc and IXa. The methodology used to estimate hake discards for Portugal and Spain since 2003 was based on the one proposed in the “Workshop on Discard Sampling Methodology and Raising Procedures” (PGCCDBS, Denmark, 2003). Spain presents results for the years 1994, 1997, 1999, 2000, 2003 and 2004. In the Portuguese Program, 2004 is the first year with an analysis of discard data. The number of trips sampled by the Spanish program for 2004 was 53, distributed by three trawl fleets- BACA trawl, Pair trawl and WHVO trawl. Portuguese onboard-observers sampled 40 trips distributed by Crustacean and Fish trawl fleets. The estimated percentages of discarded hake in relation to total catch were of 19,9 (C.V. = 22.6%) and 46,7 (C.V. = 72.1%) for the Spanish and Portuguese fleets respectively. The confidence interval for the Portuguese discard estimate is very large which denotes the very low precision of the obtained value. A co-operation in the analysis of this kind of data, between the two countries, could be the next step, since a standardisation of the methods would be of great importance for a realistic comparison of results obtained from both programs.